Case report Recurrent hoarseness in a 12-year-old female patient with pachyonychia congenita type 1: case report and literature review - Hogendorf, Anna; Wojtkiewicz-Malicka, Małgorzata; Niebudek-Bogusz, Ewa; Cywińska-Bernas, Agnieszka; Kaszuba, Andrzej; Zeman, Krzysztof (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2012)
We report a phoniatric evaluation of a 12-year-old female with pachyonychia congenita type 1 (Jadassohn-Lewandowsky syndrome) and recurrent hoarseness. Pachyonychia congenita (PC) is an ultra rare genetic disorder of keratinisation that predominantly affects not only the nails, skin, hair, but also oral mucosae and larynx. Hoarseness is reported in 16% of patients with this disease and is attributed to laryngeal leukoplakia. However, assessment of this symptom in most PC cases is subjective and a detailed phoniatric assessment of patients with PC and hoarseness has not been described in the literature so far.